Protective Effects of Diallyl Sulfide and Curcumin Separately against Thallium-Induced Toxicity in Rats - Mohamed M. Abdel-Daim; Rania H. Abdou (Cell Journal, 2015)
Thallium acetate (TI) is a cumulative poison intimately accompanied by an increase in reactive oxygen species (ROS) formation that represents an important risk factor for tissue injury and malfunction. This study aims to determine the possible hepatoprotective and antioxidant effects of diallyl sulfide (DAS) from garlic and curcumin from turmeric against TI-induced liver injury and oxidative stress (OS) in rats. This in vivo animal study divided rats into six groups of 8 rats per group. The first group received saline and served as the control group. The second and third groups received DAS or curcumin only at a dose of 200 mg/kg. The fourth group received TI at a dose of 6.4 mg/kg for 5 consecutive days. The fifth and sixth groups received DAS or curcumin orally 1 hour before TI intoxication at the same dose as the second and third groups. Liver integrity serum enzymes aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), and γ-glutamyltransferase (γ-GT) were evaluated. Serum and liver tissue homogenate lipid peroxidation and OS biomarkers were measured. The data were analyzed by one-way ANOVA followed by Duncan’s multiple range test for post hoc analysis using SPSS version 16. TI induced marked oxidative liver damage as shown by significantly (P≤0.05) elevated serum AST, ALT, ALP, LDH and γ-GT levels. There were significant (P≤0.05) increases in serum and hepatic malondialdehyde (MDA) and serum nitric oxide (NO) as well as decreased hepatic glutathione (GSH) and catalase (CAT) activities. There were significantly (P≤0.05) less serum and hepatic superoxide dismutase (SOD) and total antioxidant capacity (TAC). Pre-treatment with DAS or curcumin ameliorated the changes in most studied biochemical parameters. DAS and curcumin effectively reduced TI-induced liver toxicity.